Integrasi Axiomatic Design, design for manufacture and assembly, dan rekayasa serempak dalam Desain Produk - Chenio, Alkent; Ginting, Rosnani; Ishak, Aulia (Institut Seni Indonesia Yogyakarta, 2025)
Product design faces challenges where designers need to know the parameters before the design process to minimize product development time, and products that are not suitable for manufacturing cause losses. This research is a narrative literature review of the integration of Axiomatic Design (AD), Design for Manufacture and Assembly (DFMA), and Concurrent Engineering (CE) to see the potential of integrating the three methods in product design. Eight journals from the last decade were analyzed to evaluate the impact of integration on product design. Results showed that the integration of the three methods was able to reduce the required design iterations along with a reduction in manufacturing costs and assembly time. The integration was able to identify and break down functional requirements with cross-functional collaboration from the early stages of design as well as streamlining the product and assembly process. In addition, the integration also provides manufacturing information for designers so that the product design is compliant from the manufacturing side. The combination of the three methods results in products that are easier to manufacture, reduce lead times and product costs. Therefore, this approach is highly recommended for the manufacturing industry to improve cost efficiency, time, and product quality.